Psychological readiness for innovative activity and the ability to self-management of the police chiefs - O. M. Voluiko (Law and Safety)
It has been substantiated that modern realities dictate new requirements to the personality of a chief within law enforcement agencies, especially when his management activity is carried out in conditions that are characterized by their uncertainty, tension and responsibility. The effectiveness and success of the entire law enforcement system, as well as the quality of performing police professional tasks depend on the capabilities and personal qualities and competencies of a police chief. And the ability to act quickly in a changing environment and psychological readiness for innovative activity should provide a chief with the opportunity to improve the police work.